Factors influencing integration of information and communication technology (ICT) in teaching and learning in primary schools - T Mohamed, Norsidah; Mahmud, Rosnaini; Nawawi, Mokhtar (Faculty of Educational Studies, Universiti Putra Malaysia, 2015)
This study aims to identify the presence of factors which support the ICT integration in teaching and learning. The eight factors studied were based on Ely’s framework namely dissatisfaction with the status quo, (ii) knowledge and skills, (iii) resources, (iv) rewards or incentives, (v) time, (vi) participation, (vii) commitment, and (viii) leadership. This study was quantitative descriptive in nature and utilized questionnaire as the instrument for data collection. The reliability of the research instrument was more than .68. The research respondents were 317 teachers from a state in Malaysia. Analysis found that seven out of the eight factors were present and supported ICT integration namely: knowledge and skills, leadership, commitment, dissatisfaction with the status quo, participation, time, and rewards and incentives. Resources were identified as the factor that was not supportive for the integration of ICT.